2019
DOI: 10.3390/cells8030217
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Interactions between the Glucocorticoid Receptor and HDAC2 Regulate Osteocalcin Expression in VPA-Treated MSCs

Abstract: Epigenetic regulation has been considered an important mechanism for influencing stem cell differentiation. In particular, histone deacetylases (HDACs) have been shown to play a role in the osteoblast differentiation of mesenchymal stem cells (MSCs). In this study, the effect of the HDAC inhibitor, valproic acid (VPA), on bone formation in vivo by MSCs was determined. Surprisingly, VPA treatment, unlike other HDAC inhibitors, produced a well-organized lamellar bone tissue when MSCs–collagen sponge constructs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 68 publications
(79 reference statements)
1
32
0
Order By: Relevance
“…Several studies have reported that glucocorticoid receptor (GR) is critical for this regulation. HDAC2 binds to GR and inhibits its translocation into the nucleus, but when HDAC2 is inhibited by VPA, GR can enter the nucleus and thus affect the expression of the OC [ 141 , 142 ]. Suberoylanilide hydroxamic acid (SAHA), a pan inhibitor of HDACs, increases the expression of DSPP via the activation of Nfic and enhances odontogenic differentiation in DPSCs [ 143 ].…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…Several studies have reported that glucocorticoid receptor (GR) is critical for this regulation. HDAC2 binds to GR and inhibits its translocation into the nucleus, but when HDAC2 is inhibited by VPA, GR can enter the nucleus and thus affect the expression of the OC [ 141 , 142 ]. Suberoylanilide hydroxamic acid (SAHA), a pan inhibitor of HDACs, increases the expression of DSPP via the activation of Nfic and enhances odontogenic differentiation in DPSCs [ 143 ].…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…Additionally, chromatin immunoprecipitation (ChIP) assays confirmed the role of GR in OC downregulation, showing recruitment of GR to the nGRE element in the OC promoter. These results open new directions in targeted therapies and offer new insights into the regulation of MSCs fate determination [12].…”
Section: Stem Cells and Muscle Diseasesmentioning
confidence: 90%
“…The second young researcher of this session was Dr. Marcella La Noce (University of Campania, Napoli, Italy) who spoke about adult stem cells isolated from the dental pulp which is an interesting source of postnatal progenitor cells and stem cells [12]. The aim of this study was to evaluate the osteogenic differentiation of dental pulp stem cells (DPSCs) treated with the following different histone deacetylase inhibitors (HDACi): Valproic acid (VPA), entinostat (MS275), trichostatin A (TSA), and vorinostat (SAHA).…”
Section: Stem Cells and Muscle Diseasesmentioning
confidence: 99%
“…In particular, their osteogenic and odontoblastic differentiation potential for intramembranous bone TE and dentistry applications is the most extensively studied (Anitua et al, 2018;Gronthos et al, 2000;La Noce et al, 2019;Morad et al, 2013;Nuti et al, 2016;Paino et al, 2017). In contrast, the chondrogenic potential of DPSCs for TE applications remains underexplored as most studies investigating DPSCs have only addressed their chondrogenesis as part of their multilineage differentiation potential for human (Hilkens et al, 2013;Koyama et al, 2009;Mokry et al, 2010;Takebe et al, 2017;Zhang et al, 2006), murine (Grottkau et al, 2010) and porcine cells (Iohara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%